Combining bottleneck analysis and quality improvement as a novel methodology to improve the quality of neonatal care in a northeastern state of India: a feasibility study. Issue 1 (22nd September 2018) - Datta, Vikram; Srivastava, Sushil; Garde, Rahul; Tluangi, Lalrin; Giri, Hunsi; Sangma, Sangeeta; Burman, Himesh; Pahwa, Parika; Pemde, Harish; Livesley, Nigel
Abstract: Background: The State of Meghalaya, India, has some of the worst newborn health outcomes in the country. State health authorities commissioned an assessment of newborn service delivery to improve services. This study proposes bottleneck analysis (BNA) and quality improvement (QI) methods as a combined method to improve compliance with evidence-based neonatal interventions in newborn health facilities. Methods: An adapted Every Newborn BNA tool was applied to collect data on barriers to providing quality care in five district hospitals. Subsequently, health workers were coached to use QI methodology to overcome identified bottlenecks. Data from QI projects were analysed using run charts. Results: BNA revealed that interventions directed toward basic newborn care and special newborn care facilities needed attention. Facilities that undertook QI projects showed an improvement in neonates having early initiation of breastfeeding within the first hour of birth, from 64% to a peak of 94% in one facility and from 75% to 91% in another. Skin-to-skin contact increased from 49% to a peak of 78% and is sustained at 58%. Improved performance has been sustained in some facilities. Conclusions: The combination of BNA and QI is a successful method for identifying and overcoming bottlenecks in newborn care in resource-limited settings.